2011
DOI: 10.1097/phh.0b013e3182053f1b
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs Among People Reported With Hepatitis C, New York City

Abstract: This hepatitis C surveillance project, with information from patients and clinicians, illustrates a valuable use of a chronic hepatitis C surveillance system. The patients described here had several unmet needs, including hepatitis A and B vaccination, basic information about the virus, support groups, and counseling about preventing further liver damage and preventing transmission to others. Relatively simple and affordable health department activities can address these needs, improving quality of life and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…DOHMH further described patients' unmet needs in terms of education, vaccination, support groups, and RNA testing to share with other stakeholders who address these needs. 30,31 The 2010 IOM report's call to action proposes that health departments investigate all acute and chronic HCV and HBV cases. However, the volume of newly reported HCV cases annually in NYC would require 35,000 person-hours a year, which far exceeds available resources.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DOHMH further described patients' unmet needs in terms of education, vaccination, support groups, and RNA testing to share with other stakeholders who address these needs. 30,31 The 2010 IOM report's call to action proposes that health departments investigate all acute and chronic HCV and HBV cases. However, the volume of newly reported HCV cases annually in NYC would require 35,000 person-hours a year, which far exceeds available resources.…”
Section: Resultsmentioning
confidence: 99%
“…Similar sampling has been used for previous HCV projects and for surveillance on other highvolume diseases such as chronic hepatitis B, influenza, Lyme disease, and gonorrhea. 30,[32][33][34][35] We believe that the IOM's goals can be achieved through additional funding to continue and improve this type of enhanced surveillance system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most articles included in this review, the reported unmet supportive care needs of patients are the investigators’ interpretations of patients’ needs, as patients were not specifically asked to report their perceived unmet supportive care needs or concerns, rather asked whether they had been counselled about not drinking alcohol and how to avoid transmitting the virus to other people. 41 Those patients who had not been counselled may not necessarily perceive this as an unmet need or concern. In Gifford et al 's 40 study, a large number of women reported ever having symptoms and rated their health as ‘fair-poor’, yet some women may have received outside help or support to deal with these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Similar sampling methods have been used for HCV and other public health surveillance projects in the past. [20][21][22][23] We sampled a relatively small number to ensure that sufficient staff time was available for investigations to be thorough. Our staff was able to followup with all clinicians known to have seen the patient, including those mentioned by reporting clinicians and by patients themselves.…”
Section: Discussionmentioning
confidence: 99%